2016
DOI: 10.1111/ahg.12183
|View full text |Cite
|
Sign up to set email alerts
|

HLA Alleles are Genetic Markers for Susceptibility and Resistance towards Leprosy in a Mexican Mestizo Population

Abstract: Despite the use of multidrug therapy, leprosy remains endemic in some countries. The association of several human leucocyte antigen (HLA) alleles and gene polymorphisms with leprosy has been demonstrated in many populations, but the major immune contributors associated to the spectrum of leprosy have not been defined yet. In this study, genotyping of HLA-A, -B, -DR, and -DQ alleles was performed in leprosy patients (n = 113) and control subjects (n = 117) from the region with the highest incidence for the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Several members belonging to the classical class I and class II HLA genes have been shown to be associated with leprosy. Leprosyassociated class I HLA genes include HLA-A * 28 in Mestizo populations (121) and HLA-B * 15 and HLA-C * 05 in the Brazilian population (122). Leprosy-associated class II HLA genes include HLA-DQA1 in Brazilians (123), HLA-DQB1 * 06 and HLA-DQB1 * 07 in Mestizo populations (121), HLA-DRB1 * 11 in Brazilians (124), HLA-DRB1 * 1501 in Chinese and Indians (125,126), and HLA-DRB1 * 1501 in Indians (125,126).…”
Section: The Hereditability Of Leprosy Genetic Risk Factors Associatimentioning
confidence: 99%
See 1 more Smart Citation
“…Several members belonging to the classical class I and class II HLA genes have been shown to be associated with leprosy. Leprosyassociated class I HLA genes include HLA-A * 28 in Mestizo populations (121) and HLA-B * 15 and HLA-C * 05 in the Brazilian population (122). Leprosy-associated class II HLA genes include HLA-DQA1 in Brazilians (123), HLA-DQB1 * 06 and HLA-DQB1 * 07 in Mestizo populations (121), HLA-DRB1 * 11 in Brazilians (124), HLA-DRB1 * 1501 in Chinese and Indians (125,126), and HLA-DRB1 * 1501 in Indians (125,126).…”
Section: The Hereditability Of Leprosy Genetic Risk Factors Associatimentioning
confidence: 99%
“…Leprosyassociated class I HLA genes include HLA-A * 28 in Mestizo populations (121) and HLA-B * 15 and HLA-C * 05 in the Brazilian population (122). Leprosy-associated class II HLA genes include HLA-DQA1 in Brazilians (123), HLA-DQB1 * 06 and HLA-DQB1 * 07 in Mestizo populations (121), HLA-DRB1 * 11 in Brazilians (124), HLA-DRB1 * 1501 in Chinese and Indians (125,126), and HLA-DRB1 * 1501 in Indians (125,126). In addition, other antigen-processing and presentation-related genes were found to be associated with leprosy, such as the MICA gene (127), MICB gene (127), HLA-G gene (128), and TAP1 gene (129).…”
Section: The Hereditability Of Leprosy Genetic Risk Factors Associatimentioning
confidence: 99%
“…Although leprosy is of infectious etiology, studies have demonstrated that a genetic component and its variability serve a crucial role in the establishment and progression of the disease (5,6). In previous reports, our group observed that human leukocyte antigen (HLA)-DRB1*01 and HLA-A*28 alleles were associated with susceptibility to leprosy, whereas HLA-DRB1*08 was associated with resistance, in a Mexican mestizo population (23,24). The rs2476601 polymorphism of PTPN22 has been associated with a negative regulatory function in T-cell signaling and with autoimmune diseases including type 1 diabetes (25), rheumatoid arthritis (26) and systemic lupus erythematosus (27), and several infectious diseases including tuberculosis and leprosy (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 88%
“…Polimorfismos em LACC1 constituem fator de risco devido à redução da sinalização via LACC1-NOD215. Outro exemplo é o gene HLA-A*28, relacionado com a forma clínica dimorfa e virchowiana 16 . Outros polimorfismos associados ao início da polarização para as formas clínicas ainda estão sendo pesquisados 17 .…”
Section: Fatores Biológicosunclassified